N-CAM expression: The study of muscle disease in a tertiary center of Thailand - Kanyarat Laoyoung; Phu Waisayarat; Charungthai Dejthevaporn; Chaiyos Khongkhatithum; Jariya Waisayarat (My University, 2020)
Abstract Objectives To evaluate the correlation between N-CAM expression and diagnosis of common muscle diseases in the Thai population. Methods The expression of N-CAM was interpreted in 75 muscle biopsy specimens diagnosed with myopathies in a 3-year retrospective study. We used anti-CD56 (MRQ-42) rabbit monoclonal primary antibody (1:200, Cell Marque, MilliporeSigma, Rocklin, CA, USA) in our immunohistochemical study. Results Of our 75 patients, 41 cases were female and 34 were male. The mean age of the patients was 35-year-old, with the range from 3 months to 83 years. 35 (46.67%) of the specimens were N-CAM-positive, and 40 (53.33%) were N-CAM-negative. There were 35 (46.67%) cases diagnosed with nonspecific myopathy, 17 (22.67%) with inflammatory myopathy, 9 (12.00%) with neurogenic dystrophy, 7 (9.33%) with muscular dystrophy, 5 (6.67%) with non-diagnostic myopathy, and 2 (2.67%) with mitochondrial myopathy. Chi-squared testing was used to analyze the N-CAM expression data and the diagnosis. There is a statistically significant correlation between inflammatory myopathy and N-CAM positivity (p-value <0.001, OR 14.250, 95% CI 2.960-68.606), with 15 out of 17 cases being N-CAM-positive. N-CAM was also positive in muscular dystrophy, neurogenic myopathy, and nonspecific myopathy but they were not statistically significant. We did not find N-CAM expression in our 2 mitochondrial myopathy cases, nor in the 5 non-diagnostic myopathy cases. Conclusion N-CAM expression can be a complementary tool for diagnostic evaluation in muscle diseases with regeneration or denervation of muscle fibers. We recommend further study in a larger group.
Keywords: Inflammatory myopathy; Inflammatory Myopathies and Dermatomyositis